Reactivity studies of a masked three-coordinate vanadium(II) complex - Tran, Ba L.; Singhal, Madhavi; Park, Hyunsoo; Lam, Oanh P.; Pink, Maren; Krzystek, J.; Ozarowski, Andrew; Telser, Joshua; Meyer, Karsten; Mindiola, Daniel J. (Angewandte Chemie International Edition, 2010)
An arene interaction can mask a low-valent and low-coordinate V complex, [(nacnac)V(Ntol)] (see structure), which allows for facile coordination of terminal ligands on the vanadium center. Small-molecule activation by this S=3/2 complex provides facile access to a wide range of ligand frameworks such as terminal V imido, V cyclopropene, V nitride, and the first V cyclo-P complex (see scheme). Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.